Endogenous growth and structural change through vertical and horizontal innovations - Anton Bondarev; Alfred Greiner (University of Basel, Center of Business and Economics (WWZ), 2017)
This paper combines horizontal and vertical innovations to generate an endogenous growth model allowing for structural change as an endogenous phenomenon. Every industry is profitable only for a limited period of time, making the effective time of existence of the technology endogenous and finite. We find that in such an economy endogenous structural change is the source of ongoing economic growth. Further, the range of existing sectors stays constat as well as growth rates as long as the technologies are symmetric.
Keywords: 330; Endogenous Growth; Creative Destruction; Arrow Replacement Effect; Endogenous Structural Change; Horizontal Innovation; Endogenous Patents